Evaluating the upper airway with standardized magnetic resonance imaging - Stuck, Boris; Köpke, Julian; Maurer, Joachim T.; Verse, Thomas; Bran, Gregor M.; Düber, Christoph; Hörmann, Karl (The laryngoscope, 2002)
Objectives/Hypothesis Magnetic resonance imaging (MRI) potentially offers various advantages in assessing the upper airway. The aims of the presented study were 1) to evaluate which anatomical parameters of upper airway soft tissue morphology (distances, areas, volumes) could be defined using MRI scans, 2) to examine the stability or variability of these parameters over time and between different investigators, and 3) to develop a standardized protocol for MRI measurements of the upper airway. Study Design Prospective clinical trial. Methods Twenty-four scans were performed on six healthy subjects over a period of 4 weeks. Various parameters such as tongue dimensions, volumes and spaces, posterior airway spaces, and soft palate dimensions were established, and their variation over time between different investigators and with repeated analysis was assessed. Results All the parameters were of high stability and reproducibility. The time of day had no significant influence on the results. An abbreviated method for the evaluation of the tongue volume was developed. Four-millimeter slices with a conventional MRI scan generate pictures of high quality in a maintainable acquisition time. Conclusions We were able to evaluate which anatomical parameters of upper airway could be defined using MRI scans. The variability of these parameters over time and between different investigators was assessed. We developed a standardized protocol for MRI measurements of the upper airway. Standardized protocols are mandatory, and the variability of the measurements must be taken into account if results of different clinical centers must be compared or if changes after therapeutic interventions are to be investigated.